Ca2+and Ca2+-activated K+ channels that support and modulate transmitter release at the olivocochlear efferent-inner hair cell synapse - De San Martín, J.Z. (2010)
In the mammalian auditory system, the synapse between efferent olivocochlear (OC) neurons and sensory cochlear hair cells is cholinergic, fast, and inhibitory. This efferent synapse is mediated by the nicotinic α9α10 receptor coupled to the activation of SK2 Ca 2+-activated K+ channels that hyperpolarize the cell. So far, the ion channels that support and/or modulate neurotransmitter release from the OC terminals remain unknown. To identify these channels, we used an isolated mouse cochlear preparation and monitored transmitter release from the efferent synaptic terminals in inner hair cells (IHCs) voltage clamped in the whole-cell recording configuration. Acetylcholine (ACh) release was evoked by electrically stimulating the efferent fibers that make axosomatic contacts with IHCs before the onset of hearing. Using the specific antagonists for P/Q- and N-type voltage-gated calcium channels (VGCCs), ω-agatoxin IVA and ω-conotoxin GVIA, respectively, we show that Ca2+ entering through both types of VGCCs support the release process at this synapse. Interestingly, we found that Ca2+ entering through the dihydropiridine-sensitive L-type VGCCs exerts a negative control on transmitter release. Moreover, using immunostaining techniques combined with electrophysiology and pharmacology, we show that BK Ca2+-activated K+ channels are transiently expressed at the OC efferent terminals contacting IHCs and that their activity modulates the release process at this synapse. The effects of dihydropiridines combined with iberiotoxin, a specific BK channel antagonist, strongly suggest that L-type VGCCs negatively regulate the release of ACh by fueling BK channels that are known to curtail the duration of the terminal action potential in several types of neurons. Copyright © 2010 the authors.